(E)-N′-[1-(4-Aminophenyl)ethylidene]benzohydrazide - Shan, Shang (International Union of Crystallography, 2008)
Crystals of the title compound, C(15)H(15)N(3)O, were obtained from a condensation reaction of benzohydrazide and 1-(4-aminophenyl)ethanone. The molecule assumes an E configuration with the aminophenyl and benzohydrazide units located on opposite sites of the C=N double bond. In the crystal structure, the benzene rings of the molecule are slightly twisted with respect to the central hydrazide, the dihedral angles being 18.22 (12) and 27.62 (12)°. The crystal structure contains intermolecular N—H⋯O and weak C—H⋯N hydrogen bonding.